ANALISIS KEBUTUHAN DAN KETERSEDIAAN AIR IRIGASI PADA DAERAH IRIGASI KADIBESO KABUPATEN BANTUL - , ARIF KRISTANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Meeting the needs of irrigation water in the irrigation Kadibeso area is very important to support agricultural productivity in this area. Agricultural productivity can also be maximized if the amount plants of water that need sufficient and also use regularly. This final project aims to determine the need for and water availability in the irrigation of Kadibeso areas. Calculation of crop water requirements based on consumptive use (Etc), while land preparation water requirement (IR), perlokasi (P), the replacement of the water layer (WLR), irrigation efficiency (EI), effective rainfall (Re) and irrigated acreage. Value of potential evapotranspiration (Eto) was calculated based Blaney- Criddle equation. While the calculation is based on the availability of water discharge mainstay (Q 80%) of the weir discharge data kadibeso within a period of 5 years. Reference the formula used to come in the book of applied hydrology (Bambang Triatmodjo). Calculation results obtained in the irrigation areas of kadibeso water needs of 97.388 liters / sec - 154.149 liters / sec. While the availability of water based discharge mainstay 80% is 204 liters / sec. From the results of the analysis showed that the availability of water to meet the needs of water for irrigation in irrigated Kadibeso areas.